DETERMINATION OF ASCORBIC ACID IN JUICES USING THE CHRONOAMPEROMETRY - Thakthuang, Sunantha; Sopaporn, Paradee; Meksun, Siriporn; Chitbuengphrao, Anurak; Pinwattana , Kulwadee; Preechaworapun, Anchana (PSRU Journal of Science and Technology, 2021)
The present work aims to determine the amount of ascorbic acid using chronoamperometry by glassy carbon electrode. The Electrochemical behavior and quantitative determination of ascorbic acid was carried out in phosphate buffer solution (pH 6.0). Electrochemical behavior of ascorbic acid has been studied by cyclic voltammetry, which the anodic peak of ascorbic acid was observed at the potential of 0.30 Volt, at scan rate of 0.10 Volt per second. Chronoamperometric detection of ascorbic acid showed the linear response in the range of 10 to 340 micromolar at 0.30 Volt. Moreover, the proposed method was successfully applied to real sample analyze as lemon and orange juices.